PERANAN SUBSEKTOR KEHUTANAN DALAM PEMBANGUNAN EKONOMI DI KALIMANTAN BARAT - Satria Astana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Forestry sub-sector has an important contribution to economic development of West Kalimantan. For the last few years the average contribution per year in the gross domestic regional product, the manpower absorbtion, the social income earning, the regional income earning, and the foreign exchange earning of the region is estimated around 11.20%, 66.69%, 81.91%, 47.9 7%, and 58.79%, respectively. The contribution elasticities of the five economic variables mentioned are 0.83, 1.03, 1.06, 0.94, and 0.75, respectively. For the next nine years, the contribution will be still possible to raise the economic growth of the region. After that periode, however, it will not be the anymore without a substantial progress in development of both the production forest resource and the secondary wood industry.